The Remains of the Body: Human Tissue, Competence and Consent in an Age of Profit - Kluge, Eike-Henner (Operating Room Nurses Association of Canada Journal, 2008)
Over the past few decades human tissues and fluids have increasingly become of interest to health-oriented research due to their potential use in the development of new diagnostic tools, drugs and treatment modalities.